Os efeitos da renda e da desigualdade na redução da extrema indigência no Brasil - Coelho, José Alves (2009)
Poverty reduction is closely related to what happens to income inequality and average, and the big question to identify which policies of economic growth are more effective to reverse this situation most quickly, if policies that encourage the growth of average income of the economy or policies that encourage the reduction of inequality among individuals. This study estimates the income elasticity and inequality for the segment of the Brazilian population in extreme poverty based on PNAD the period 1995 to 2007. The elasticities show that, for Brazil, policies to combat extreme poverty through the reduction of inequality have a greater impact than the increase in income. Furthermore, based on the effect in the regions of Brazil, it appears that for the North and Northeast elasticity inequality is much more sensitive than the income elasticity, while in the South, Southeast and Midwest notes the increase in income elasticity and declining inequality elasticity compared with Brazil and the North and Northeast. Still, in the South, Southeast and Midwest have the effect of inequality is higher than the income effect, the example of the results found for Brazil and the North and Northeast. In addition, other models estimated considering a dummy to capture the effect of the FHC and Lula governments, the result suggests a negative effect on poverty, and this represents the period from 2003 to 2007 poverty fell. In general, the results suggest that the reduction of inequality has a much more significant than the increase in the income section of the population in extreme poverty.